1997
DOI: 10.1007/bf02303577
|View full text |Cite
|
Sign up to set email alerts
|

Delayed shoulder exercises in reducing seroma frequency after modified radical mastectomy: A prospective randomized study

Abstract: The incidence of seromas after modified radical mastectomy for breast cancer is reduced by delaying shoulder exercises one week postoperatively. Earlier postoperative physiotherapy is not necessary to avoid impaired shoulder function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
15

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 10 publications
2
54
1
15
Order By: Relevance
“…A reasonable alternative approach endorsed by most breast surgeons is to recommend that patients simply limit motion at the shoulder to abduction no greater than 90 and that active upper extremity physiotherapy be delayed until drainage catheters have been removed. This strategy seems to decrease seroma formation more effectively than early physiotherapy programs and does not adversely affect long-term range-of-motion results [30,31].…”
Section: Seromamentioning
confidence: 99%
“…A reasonable alternative approach endorsed by most breast surgeons is to recommend that patients simply limit motion at the shoulder to abduction no greater than 90 and that active upper extremity physiotherapy be delayed until drainage catheters have been removed. This strategy seems to decrease seroma formation more effectively than early physiotherapy programs and does not adversely affect long-term range-of-motion results [30,31].…”
Section: Seromamentioning
confidence: 99%
“…These include closure of dead space [8,9], use of thrombin [10], compression dressings [11,12] aspiration alone instead of drainage [13], use of collagen tissue sealants [14,15], and delaying postoperative shoulder exercises [16]. Use of ultrasonic shears for breast cancer surgery has been described as early as 2000 by Deo et al [17], in which they showed the feasibility of modified radical mastectomy using ultrasonic shears.…”
Section: Discussionmentioning
confidence: 99%
“…Mas é importante lembrar que para alguns autores a retirada precoce do dreno -muitas vezes por motivos de acidente, ar no circuito e infecção -pode ser outro fator que colabora para a formação do seroma. É provável que a incidência do seroma também esteja relacionada a outros fatores como técnica cirúrgica, infecção, tempo de cirurgia, tamanho das mamas e linfonodos comprometidos 19,23 . Observamos neste estudo alta incidência de deiscência.…”
Section: Discussionunclassified
“…Entretanto, contrariando a idéia de que o exercício livre provocasse maior afastamento das bordas cirúrgicas quando comparado ao exercício limitado, a incidência de deiscência esteve igualmente distribuída nos dois grupos. Na literatura, a deiscência está possivelmente associada a outros fatores, como presença de infecção, obesidade e idade média maior que 55 anos, condições especiais em que se faz necessário maior tempo para uma correta cicatrização 19,21,23 . Além da obesidade e idade, a presença de linfonodos comprometidos, tempo de cirurgia, diferentes técnicas cirúrgicas utilizadas e radioterapia são outros fatores possivelmente associados às complicações pós-operatórias.…”
Section: Discussionunclassified